Is alcohol septal ablation in women performed too late?. (25th November 2020) - Batzner, A; Aicha, D; Seggewiss, H
Abstract: Introduction: Alcohol septal ablation (PTSMA) was introduced as interventional alternative to surgical myectomy for symptomatic patients with hypertrophic obstructive cardiomyopathy (HOCM) 25 years ago. As gender differences in diagnosis and treatment of HOCM are still unclear we analyzed baseline characteristics and results of PTSMA in a large single center cohort with respect to gender. Methods and results: Between 05/2000 and 06/2017 first PTSMA in our center was performed in 952 patients with symptomatic HOCM. We treated less 388 (40.8%) women and 564 (59.2%) men. All patients underwent clinical follow-up. At the time of the intervention women were older (61.2±14.9 vs. 51.9±13.7 years; p<0.0001) and suffered more often from NYHA grade III/IV dyspnea (80.9% vs. 68.1%; p<0.0001), whereas angina pectoris was comparable in women (62.4%) and men (59.9%). Echocardiographic baseline gradients were comparable in women (rest 65.0±38.1 mmHg and Valsalva 106.2±45.7 mmHg) and men (rest 63.1±38.3 mmHg and Valsalva 103.6±42.8 mmHg). But, women had smaller diameters of the left atrium (44.3±6.9 vs. 47.2±6.5 mm; p<0001), maximal septum thickness (20.4±3.9 vs. 21.4±4.5 mm; p<0.01), and maximal thickness of the left ventricular posterior wall (12.7±2.8 vs. 13.5±2.9 mm; p<0.0001). In women, more septal branches (1.3±0.6 vs. 1.2±0.5; p<0.05) had to be tested to identify the target septal branch. The amount of injected alcohol was comparable (2.0±0, 4 in women vs. 2.1±0.4 ml in men). The maximum CK increase was lower in women (826.0±489.6 vs. 903.4±543.0 U / l; p<0.05). During hospital stay one woman and one man died, each (n.s.). The frequency of total AV blocks in the cathlab showed no significant difference between women (41.5%) and men (38.3%). Furthermore, the rate of permanent pacemaker implantation during hospital stay did not differ (12.1% in women vs. 9.4% in men). Follow-up periods of all patients showed no significant difference between women (5.7±4.9 years) and men (6.2±5.0 years). Overall, 37 (9.5%) women died during this period compared to only 33 (5.9%) men (p<0.05). But, cardiovascular causes of death were not significantly different between women (2.8%) and men (1.6%). Furthermore, the rates of surgical myectomy after failed PTSMA (1.3% in women vs. 2.3% in men), ICD implantation for primary prevention of sudden cardiac death according to current guidelines (4.1% in women vs. 5.9% in men) or pacemaker implantation (3.6% in women vs. 2.0% in men) showed no significant differences. Summary: PTSMA in women with HOCM was performed at more advanced age with more pronounced symptoms compared to men. While there were no differences in acute outcomes, overall long-term mortality was higher in women without differences in cardiovascular mortality. Therefore, women may require more intensive diagnostic approaches in order not to miss the correct time for gradient reduction treatment. Funding Acknowledgement: Type of funding source: None